Agronomic yield and starch properties of banana cultivars - Leonel, Magali [UNESP]; Leonel, Sarita [UNESP]; dos Santos, Thaís Paes Rodrigues [UNESP]; Souza, Jackson Mirellys Azevedo; Martins, Rafaelly Calsavara [UNESP]; da Silva, Marcela Sant’Anna Cordeiro [UNESP] (FapUNIFESP (SciELO), 2021)
The objective of this work was to evaluate the banana cultivars for their agronomic yield and starch characteristics. The experiment was carried out in a randomized complete block design, with a factorial arrangement of two cultivars (’BRS Conquista’ and ‘BRS Platina’) and two crop cycles, with three plants per treatment, and five replicates. Fruit yield and starch quality were evaluated. ‘BRS Conquista’ showed smaller fruit; however, it had a greater marketable bunch weight and yield than ‘BRS Platina’. Starches differed for the main physicochemical characteristics, except for X-ray diffraction pattern (B type) and phosphorus content (0.0058−0.0060%). ‘BRS Platina’ stood out for its higher content of resistant starch (74.55%) that differed from the starch isolated from ‘BRS Conquista’. However, the starch of ‘BRS Conquista’ showed the following characteristics: larger granules (34.74 µm), with greater crystallinity (33.64%); less swelling power and solubility (26.77 g g-1 and 19.21%, respectively); and greater breakdown, setback and final viscosity (67.06, 182.42, and 341.39 RVU, respectively). ‘BRS Conquista’ shows favorable production characteristics for processing to obtain starch. The higher resistant starch content of ‘BRS Platina’ may commercially justify its lower agronomic yield. Starches of the two cultivars show desirable characteristics for different industrial applications.
Rendimento agronômico e propriedades de amido de cultivares de banana
Keywords: BRS Conquista; BRS Platina; características físico-químicas; Musa; physicochemical characteristics